2022
DOI: 10.1101/2022.03.02.482509
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Classifying interactions in a synthetic bacterial community is hindered by inhibitory growth medium

Abstract: Predicting the fate of a microbial community and its member species relies on understanding the nature of their interactions. However, designing simple assays that distinguish between interaction types can be challenging. Here, we performed spent media assays based on the predictions of a mathematical model to decipher the interactions between four bacterial species: Agrobacterium tumefaciens (At), Comamonas testosteroni (Ct), Microbacterium saperdae (Ms) and Ochrobactrum anthropi (Oa). While most experimental… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(8 citation statements)
references
References 66 publications
1
7
0
Order By: Relevance
“…We reran our original experiment in a plate reader to obtain higher time resolution, and indeed, we found a significant difference in the final yields of C. testosteroni in MM and the pure SM of A. tumefaciens ( P < 0.01) and M. saperdae ( P < 0.001) as well as a small “bump” at the beginning of the SM growth curves ( Fig. 4F , arrows) (complete statistical results on the final yield and the length of the lag phase are available in reference 32 ). These two features, obtained by high-resolution growth curve measurements until stationary phase, make it possible to distinguish between cross-feeding and cross-detoxification without the need for further molecular analyses.…”
Section: Discussionsupporting
confidence: 58%
See 4 more Smart Citations
“…We reran our original experiment in a plate reader to obtain higher time resolution, and indeed, we found a significant difference in the final yields of C. testosteroni in MM and the pure SM of A. tumefaciens ( P < 0.01) and M. saperdae ( P < 0.001) as well as a small “bump” at the beginning of the SM growth curves ( Fig. 4F , arrows) (complete statistical results on the final yield and the length of the lag phase are available in reference 32 ). These two features, obtained by high-resolution growth curve measurements until stationary phase, make it possible to distinguish between cross-feeding and cross-detoxification without the need for further molecular analyses.…”
Section: Discussionsupporting
confidence: 58%
“…As LC-MS yielded only the relative abundances of each compound, we added several concentrations to C. testosteroni growing in MM. We found that a range of concentrations shortens the lag phase of C. testosteroni significantly (oxoglutarate, 0.39 mM to 12.5 mM; proline, ≥0.39 mM; hypoxanthine, ≥0.62 mM [complete statistical results are available in reference 32 ]). At high-enough concentrations, all three metabolites also increased the final yield of C. testosteroni , suggesting that they act as carbon sources (oxoglutarate, 0.09 mM to 12.5 mM; proline, ≥0.78 mM; hypoxanthine, ≥1.25 mM [complete statistical results are available in reference 32 ]).…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations